2018
DOI: 10.1007/s00380-018-1135-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood urea nitrogen-to-creatinine ratio at hospital admission and long-term mortality in patients with acute decompensated heart failure

Abstract: Although elevated blood urea nitrogen (BUN)-to-creatinine (BUN/Cr) ratio at hospital admission has been reported to be associated with poor short-term prognosis, its association to long-term mortality in patients with acute decompensated heart failure (ADHF) remains to be elucidated. Moreover, an additive prognostic value to preexisting renal markers including creatinine and BUN has not been well described. A cohort of 557 consecutive ADHF patients admitted to the cardiac intensive care unit was studied. All c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 27 publications
0
46
0
3
Order By: Relevance
“…The main finding of this study is that AHF combined with elevated BUN/Cr was associated with an increased risk of long-term mortality in patients with AMI. [12,15] In addition, our findings suggest that the predictive value of BUN/Cr combined with AHF for the prognosis of patients with AMI is not weaker than that of the Grace risk score.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The main finding of this study is that AHF combined with elevated BUN/Cr was associated with an increased risk of long-term mortality in patients with AMI. [12,15] In addition, our findings suggest that the predictive value of BUN/Cr combined with AHF for the prognosis of patients with AMI is not weaker than that of the Grace risk score.…”
Section: Discussionmentioning
confidence: 67%
“…Both the renin-angiotensin-aldosterone system (RAAS) and sympathetic nervous system (SNS) were activated in patients with AHF, which could promote absorption of water and sodium and cause passive reabsorption of BUN in the renal tubules. [4,12] Activation of the neurohormonal system could also lead to renal vasoconstriction and decreased glomerular filtration rate and BUN excretion. [12] Furthermore, insufficient blood volume secondary to low cardiac output stimulates the release of arginine vasopressin (AVP), which can facilitate the reabsorption of BUN in the collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…Similar, Kirtane et al demonstrated that patients hospitalized with acute coronary syndrome and elevated serum urea levels were on average older, had a higher prevalence of co-morbidities and an increased short and long-term mortality rate 28 . In extension of these populations, an increased urea-to-creatinine ratio is also associated with worsening of renal function and all-cause mortality after hospitalization for acute heart failure 19,20 and long-term mortality among patients undergoing dialysis 21 . Thus, a higher urea-to-creatinine ratio might identify older, frail patients with an increased risk for long-term all-cause mortality after hospital discharge.…”
Section: Adj Hr (95% Ci) a P-valuementioning
confidence: 99%
“…Among emerging techniques, BIVA has been demonstrated to be a simple and fast method for the assessment of body peripheral hydration status [6], providing prognostic information in HF patients [9][10][11]. Nevertheless, evidence also suggested that higher values of the BUN/Cr ratio are associated with "venous" congestion [7,12], and, in parallel, these values demonstrated prognostic impacts in HF patients independent of creatinine levels and glomerular filtration rate [7,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%